Salt-Tolerant PGPR Confer Salt Tolerance to Maize Through Enhanced Soil Biological Health, Enzymatic Activities, Nutrient Uptake and Antioxidant Defense - Shabaan, Muhammad; Asghar, Hafiz Naeem; Zahir, Zahir Ahmad; Zhang, Xiu; Sardar, Muhammad Fahad; Li, Hongna (Frontiers in Microbiology, 2022)
Salt tolerant plant growth-promoting rhizobacteria (PGPR) can improve soil enzyme activities which are indicators of the biological health of the soil and overcome the nutritional imbalance in plants. A pot trial was executed to evaluate the effect of inoculation of different salt-tolerant PGPR strains in improving soil enzyme activities. Three different salinity levels (original, 5 and 10 dS m-1) were used, and maize seeds were coated with the freshly prepared inocula of ten different PGPR strains. Among different strains, inoculation of SUA-14 (Acinetobacter johnsonii) caused a maximum increment in urease (1.58 fold), acid (1.38 fold) and alkaline phosphatase (3.04 fold) and dehydrogenase (72%) activities as compared to their respective uninoculated control. Acid phosphatase activities were found to be positively correlated with P contents in maize straw (r = 0.96) and grains (r = 0.94). Similarly, a positive correlation was found between alkaline phosphatase activities and P contents in straw (r = 0.77) and grains (r = 0.75). In addition, urease activities also exhibited positive correlation with N contents in maize straw (r = 0.92) and grains (r = 0.91). Moreover, inoculation of Acinetobacter johnsonii caused a significant decline in catalase (39%), superoxide dismutase (26%) activities and malondialdehyde contents (27%). The PGPR inoculation improved the soil's biological health and increased the uptake of essential nutrients and conferred salinity tolerance in maize. We conclude that inoculation of salt-tolerant PGPR improve soil enzyme activities and soil biological health, overcome nutritional imbalance and thereby, improve nutrient acquisition by the plant under salt stress.